2018
DOI: 10.1136/bmjopen-2017-019292
|View full text |Cite
|
Sign up to set email alerts
|

Designing PrEP and early HIV treatment interventions for implementation among female sex workers in South Africa: developing and learning from a formative research process

Abstract: ObjectivesThe objective of this research was to design relevant, tailored oral pre-exposure prophylaxis (PrEP) and early antiretroviral (ART) interventions for female sex workers (FSWs) in South Africa. This paper examines the methods, process and outcomes of employing an inductive approach to formative research exploring intervention feasibility and acceptability.SettingResearch was conducted in several sex work-related settings including five sites in and around clinics and stakeholder offices.ParticipantsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Although motivated to use PrEP, participants in our study noted adherence, stigma, and side effects as perceived barriers affecting their uptake and continued PrEP use, which was also found among FSW in Kenya and South Africa (Eakle et al, 2018; Restar et al, 2017). A study of serial interviews with FSW in South Africa also found FSW had concerns regarding adherence, but that over time participants became more committed to adherence PrEP and developed strategies and support systems (Eakle et al, 2019).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Although motivated to use PrEP, participants in our study noted adherence, stigma, and side effects as perceived barriers affecting their uptake and continued PrEP use, which was also found among FSW in Kenya and South Africa (Eakle et al, 2018; Restar et al, 2017). A study of serial interviews with FSW in South Africa also found FSW had concerns regarding adherence, but that over time participants became more committed to adherence PrEP and developed strategies and support systems (Eakle et al, 2019).…”
Section: Discussionsupporting
confidence: 59%
“…Most participants found PrEP acceptable and were highly motivated to use it. These findings contribute to the growing body of qualitative data indicating that FSW in sub-Saharan with high perceived susceptibility to HIV find PrEP highly acceptable and are hypothetically willing to use it (Eakle et al, 2018; Restar et al, 2017; Van der Elst et al, 2013). Participants in our study described employing a variety of HIV preventive behaviors, including condom use and STI testing, extensive knowledge on HIV, and feeling highly susceptible to HIV.…”
Section: Discussionmentioning
confidence: 62%
“…It is difficult to assess why participants drop out over time when they do not provide specific reasons themselves. However, based on what we learned here and what was learned in earlier research preparing for the TAPS study [25,26], it is likely that a combination of social dynamics around belief in PrEP and its efficacy (including stigmatization of taking ARVs as a sign of illness), personal risk assessment which may fluctuate over time, personal responsibilities which supersede clinic visits and participation in research, and potential issues with substance use probably contributed to retention. For these reasons and to further unpack the dropout seen in TAPS to help support PrEP programming, additional research is being considered to potentially interview women who were lost to follow up, to determine the reasons.…”
Section: Discussionmentioning
confidence: 94%
“…Initial interview guides were developed based on findings from a systematic review of qualitative evidence on women’s perspectives on use of female-initiated prevention products in sub-Saharan Africa [23,24], as well as results from formative research conducted in preparation for TAPS [25], including focus group discussions with potential users [26]. The premise and structure of the interview guides were based on the Modified Social-Ecological Model (MSEM) designed by Baral et al [27] to facilitate a holistic and broad inquiry.…”
Section: Methodsmentioning
confidence: 99%
“…These services include: HIV counselling and testing and condom distribution, NIMART (nurse‐initiated and managed antiretroviral treatment), tuberculosis screening, HPV screening, clinical services for minor ailments, psychosocial support, and referrals to both clinical and legal services. The clinics, services and programme are described in further detail in several other publications, including a detailed account of the formative research conducted during the design of the TAPS project .…”
Section: Methodsmentioning
confidence: 99%